2010
DOI: 10.1186/1471-2180-10-195
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of Mycobacterium tuberculosis isolates from patients with pulmonary tuberculosis in Mozambique

Abstract: BackgroundMozambique is one of the countries with the highest burden of tuberculosis (TB) in Sub-Saharan Africa, and information on the predominant genotypes of Mycobacterium tuberculosis circulating in the country are important to better understand the epidemic. This study determined the predominant strain lineages that cause TB in Mozambique.ResultsA total of 445 M. tuberculosis isolates from seven different provinces of Mozambique were characterized by spoligotyping and resulting profiles were compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 21 publications
2
43
0
4
Order By: Relevance
“…Such a finding is of general public health interest in Dakar, as Beijing strains are associated with drug resistance, rapid spread and great virulence when compared to other M. tuberculosis strains (Gomgnimbou et al, 2012). Moreover, it was recently suggested that some Manu 2 spoligotypes (which we frequently found in our study), could be the consequence of a "mixed" pattern due to concomitant Beijing and Euro-American strains (the latter comprising H, LAM, X, and T lineages) (Viegas et al, 2010). Therefore, considering the amount of Manu patterns and the possibility of mixed infections in our study, the above mentioned prevalence of Beijing strains could be an underestimation and potentially even be higher than the estimated 12%.…”
Section: Discussionsupporting
confidence: 52%
“…Such a finding is of general public health interest in Dakar, as Beijing strains are associated with drug resistance, rapid spread and great virulence when compared to other M. tuberculosis strains (Gomgnimbou et al, 2012). Moreover, it was recently suggested that some Manu 2 spoligotypes (which we frequently found in our study), could be the consequence of a "mixed" pattern due to concomitant Beijing and Euro-American strains (the latter comprising H, LAM, X, and T lineages) (Viegas et al, 2010). Therefore, considering the amount of Manu patterns and the possibility of mixed infections in our study, the above mentioned prevalence of Beijing strains could be an underestimation and potentially even be higher than the estimated 12%.…”
Section: Discussionsupporting
confidence: 52%
“…In the urban region of Cape Town, South Africa, prevalence of the ancestral strains in the local population of the MtbB strains was 1.5% (5/325), and in rural regions 1.9% (5/270) [9]. Recently, a considerable increase of MtbB prevalence was registered in south African countries such as Malawi, where prevalence of MtbB strains has reached 4.3% in 2005 [30] and in Mozambique, with a prevalence of MtbB strains in the southern region being 9.5%, considerably higher than the 2.5% observed in the north [13]. Most likely, the observed increase in prevalence of MtbB strains in other African countries is caused by spreading of modern Beijing sublineages dominant in South Africa, but this issue needs to be further addressed.…”
Section: Discussionmentioning
confidence: 68%
“…The prevalence of MtbB strains in these countries has reached 25% in South Africa [9] and 9% in Peru [12]. In contrast to these countries, the prevalence of Beijing strains in neighboring countries, like Mozambique and Brazil, is still low, representing only 7% [13,14] and 0.8% in local populations of Mtb strains [15], respectively. In this study, we aimed to investigate genotype characteristics and virulence-associated properties of the Beijing strains isolated in Mozambique and Brazil.…”
Section: Introductionmentioning
confidence: 91%
“…Manu lineage strains were reported from Saudi Arabia (2) and Tunisia (17) and more recently in a study from Egypt, where it represented as much as 27% of all isolates (15). However, according to a recent report, a fraction of Manu2 patterns could also arise due to mixed infection by a strain belonging to evolutionarily recent H, LAM, X, and T lineages with a Beijing strain, a risk that may be excluded by looking for genomic deletion of region of difference RD105, which is characteristic of the Beijing lineage (26). However, the complete absence of Beijing strains in our setting argues against this possibility.…”
Section: Resultsmentioning
confidence: 99%